Toward a circular transition in port waste streams The case of worn-out mooring lines at the Port of Norrköping - Eriksson, Linnéa; Tingfalk, Anna (My University, 2026)
Ports are key nodes in material flows and logistics networks, yet the management of complex waste streams within port environments remains largely linear and understudied. This study examines the end-of-life (EoL) management of worn mooring lines at the Port of Norrköping, Sweden, with the aim of identifying barriers, opportunities, and valuechain changes required to support more circular management. Through qualitative data collection that included interviews, email correspondence and a site visit, a total of 25 actors actively contributed to the study, with their expertise and insights on the area. The results of the value-chain mapping show that worn-out mooring lines are currently managed linearly, mixed with other complex materials and directed toward incineration. Key challenges to circularity include mixed polymer compositions, physical size, contamination from use, insufficient sorting at source, and low material volumes that limit the economic viability of dedicated circular pathways. Responsibilities for EoL management are fragmented across the value-chain, with no single actor assuming system-wide responsibility. Circular management is enabled through collaboration, particularly with upstream actors. The EoL waste management is currently treated as a local problem, but it demands a systemic perspective for a circular transition. In the current linear handling between multiple stakeholders, critical information about moorings is lost. Material characteristics and knowledge must be preserved and carried throughout the entire lifecycle. The system requires a fundamental shift in perspective, moving away from a linear materialfocused approach toward a product-oriented and systemic view to achieve higher levels of circularity. The study concludes that advancing circularity for mooring line waste requires coordinated action across the value-chain, with particular engagement from upstream actors such as rope manufacturers, regulators, and logistics service suppliers. Ports can play an important facilitating role by improving waste categorisation and fostering stakeholder collaboration.
Keywords: Circular economy; Mooring lines; End-of-life management; Port waste streams; Value-chain; Stakeholder analysis; Recycling